2015
DOI: 10.1021/acs.jmedchem.5b01664
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Biological Evaluation, and Utility of Fluorescent Ligands Targeting the μ-Opioid Receptor

Abstract: Fluorescently labeled ligands are useful pharmacological research tools for studying receptor localization, trafficking, and signaling processes via fluorescence imaging. They are also employed in fluorescent binding assays. This study is centered on the design, synthesis, and pharmacological evaluation of fluorescent probes for the opioid receptors, for which relatively few non-peptidic fluorescent probes currently exist. The known μ-opioid receptor (MOR) partial agonist, buprenorphine, was structurally elabo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(36 citation statements)
references
References 62 publications
(141 reference statements)
0
36
0
Order By: Relevance
“…1b ). 6-(((4,4-Difluoro-5-(2-thienyl)-4-bora-3 a ,4 a -diaza- s -indacene-3-yl)styryloxy)acetyl)aminohexanoic acid (BODIPY630/650-X) was preferred due to previous success with this fluorophore for Class A GPCR fluorescent ligands 28 , 36 , 37 as it has favourable excitation/emission wavelength for planned techniques. BODIPY630/650 is known to have an increased quantum yield in a lipid environment 38 and as the modelling suggests the fluorophore would reside within the membrane bilayer this would increase its brightness for imaging studies and reduce background fluorescence in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…1b ). 6-(((4,4-Difluoro-5-(2-thienyl)-4-bora-3 a ,4 a -diaza- s -indacene-3-yl)styryloxy)acetyl)aminohexanoic acid (BODIPY630/650-X) was preferred due to previous success with this fluorophore for Class A GPCR fluorescent ligands 28 , 36 , 37 as it has favourable excitation/emission wavelength for planned techniques. BODIPY630/650 is known to have an increased quantum yield in a lipid environment 38 and as the modelling suggests the fluorophore would reside within the membrane bilayer this would increase its brightness for imaging studies and reduce background fluorescence in aqueous solution.…”
Section: Resultsmentioning
confidence: 99%
“…Sulfo-Cy5 was chosen as the fluorescent tag, as previous work by Schembri et al suggested that this particular fluorophore had the least potential for inducing non-specific binding to the cell membrane. 19 The functional handles on 11 and 15 were elongated with a simple Boc-protected diamine chain, followed by global deprotection and chemoselective conjugation to sulfo-Cy5 to give the final fluorescent morphine probes 18 and 21 (Schemes 4 and 5, respectively).…”
Section: ¢ Resultsmentioning
confidence: 99%
“…This new tool compound could also be used in conjunction with the previously described smallmolecule fluorescent opioid antagonists to study the differences in ligand-receptor complexes in natively expressing systems, rather than in transfected systems. 19 ¢ EXPERIMENTAL SECTION General Deprotection Procedure A. The protected compound was dissolved in dry DCM (typically 5 mL) under an N2 atmosphere.…”
Section: ¢ Discussion and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…[6] The unique photophysical properties of cyanine dyes are used fort he photon upconversion in nanoparticles [7,8] or as contrasta gents in bioimaginga pplications. [9] Numerous examples of the utilization of cyanine fluorophores can be found in literature [2,[10][11][12][13][14][15] and their utilization is proven by thef luorescent contrasta gent indocyanine green (ICG, 1)a nd derivatives thereof (for example SIDAG [16] and cipate [17] ).…”
mentioning
confidence: 99%